MAINTAINING A CULTURE OF COURTESY AMONG INDONESIAN YOUTH IN THE DIGITAL AGE - Nabila Ravias Maharani; Clarissa Dani Gracia; Febrianti Fanda Sovia; Regita Cahyani Pamungkas; Moses Glorino Rumambo Pandin (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2022)
Background: Currently, the cultural values that Indonesian always upholds, have faded, especially among teenagers, which makes it easy for western culture to enter and undermine the value of implementing culture and national identity.  Aims: This study aims to analyze the culture of courtesy among adolescents in the digital era and provide solutions to maintain it. Method: Research samples of adolescents 17-19 years, 50 participants for questionnaires, and 2 participants for interviews. The method used is a qualitative study of literature and survey data collection techniques or questionnaires and is equipped with interviews. Results: This study resulted in less than half of the respondents still behaving impolitely. Respondents are aware of their behavior that lacks manners and provide reasons behind this behavior. Recommendation: Formal and informal education, group guidance, participation of social media companies, habit improving, 5S realizing. Limitations: 50 respondents is not enough to describe the actual situation, research limitations due to Covid-19, time constraints, respondents' targets are less specific.